The psychological impact on adult children who moved back home due to the financial consequences of COVID-19 - dos Reis, Danielle (My University, 2023)
The COVID-19 pandemic has had a significant impact on most countries across the globe. It also resulted in severe losses in various aspects of life such as work, school, and the family. Family life was particularly strongly affected by the lockdowns that were implemented to curb the spread of the virus. Many young adults returned to the parental home, experiencing a disruption in the family life cycle, because the decision to make this move delayed their transition to adulthood and parenthood. The purpose of this research study was to explore the psychological impact on such young adults of returning to their parents’ home because of the financial consequences of the COVID-19 pandemic in Gauteng, South Africa. The study drew on Family Systems theories and the Family Life Cycle model to understand this phenomenon and its impact on South African families. The participants of the study included young South African adults between the ages of 23 and 30 years. The data gathered from semi-structured interviews were analysed using thematic analysis. The findings show that many young people moved back to their parents because of economic challenges experienced as a result of difficulties related to finding or retaining employment. Moreover, the study found that the return home had negative implications for participants’ sense of independence, privacy, and mental health, despite increased emotional and financial support from parents. This influenced changes in their perceptions of adulthood, as well as a concurrent sense of stagnation and failure. The study also found that the return home of adult children led to an increase in interpersonal connectedness on the one hand, and to conflict between adult children and parents or guardians on the other, and it created a change in the parent-adult-child dynamic. The study adds to the emerging body of work on the impact of the COVID-19 pandemic on family life and functioning.
A research paper submitted in partial fulfilment for the degree of Master of Arts in the School of Human and Community Development, in the Community-Based Counselling Psychology, in the Faculty of Humanities, University of the Witwatersrand, Johannesburg, in 2023.
Keywords: Adult; Children; Covid-19 Pandemic; Financial consequences; Parental home; UCTD; SDG-3: Good health and well-being